A unified approach to simulate the creep-fatigue crack growth in P91 steel at elevated temperature under SSY and SSC conditions. (September 2021) - Lepore, Marcello A.; Maligno, Angelo R.; Berto, Filippo
Highlights: A FEM-based methodology has been developed to simulate CFCG. The material behaviour has been modelled with the Ramberg-Osgood equation. LCF properties have been used in a two-scale nonlinear model for FCG. The modified UniGrow law has been used in CFCG simulations. Abstract: The Finite Element (FE) model of a Compact Tension C(T) specimen, made of P91 steel with different values of loading conditions and holding times, has been chosen for simulating the creep-fatigue crack propagation in high temperature (625 °C). Two FE-based commercial software have been used considering both the Small-Scale Yielding (SSY) and the Small-Scale Creep conditions (SSC) so that Low Cycle Fatigue (LCF) properties and the C(t) integral have been used to perform the numerical simulations of creep-fatigue crack propagation. Hence, the elastic-plastic material behaviour of P91 steel has been modelled by means of the Ramberg-Osgood equation while the creep behaviour has been modelled with the Norton's model. To calculate numerically the crack growth rates for the creep-fatigue crack propagation, a modified version of the UniGrow model has been adopted also considering the creep-fatigue interaction. Finally, numerical and the experimental results available in the literature have been compared with each other. This work presents a general methodology for the simulation of the creep-fatigue phenomenon. The method can also be applied to structural components with complex geometry and challenging load conditions.